Courageous Voices: Using Text Sets to Inspire Change. Issue 5 (25th October 2016) - Tracy, Kelly N.; Menickelli, Kristin; Scales, Roya Q.
Abstract: This article describes how one teacher immersed her sixth graders in an intensive three‐week thematic text set unit centered on courage. Her aim was to help students discover and take action on issues that mattered to them as they learned important literacy skills and strategies. Students engaged in significant reading, writing, and discussion as they developed and enacted action plans to create positive change. Intentionally designed instruction moved from teacher‐led whole‐class lessons on the same texts to student‐led small‐group/individual learning with multiple texts. Texts included a variety of formats (e.g., picture books, songs, articles, poems) from varied reading levels.